2021
DOI: 10.1002/rcs.2230
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive ileal ureter replacement: Comparative analysis of robot‐assisted laparoscopic versus conventional laparoscopic surgery

Abstract: Background This study is an initial comparative analysis of perioperative and intermediate‐term functional outcomes between patients who underwent robot‐assisted laparoscopic (RALS) or conventional laparoscopic surgery (LS). Materials and Methods A total of 25 patients who underwent ileal ureter replacement (10 RALS and 15 LS) were followed by functional cine magnetic resonance urography (MRU) combined with a modified Whitaker test. Also, the characteristics, perioperative data and functional outcomes of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…A longer ureteral defect can be replaced using a segment of the intestines, usually the ileum (ileal interposition graft), in our department [7]. The first ileal ureter substitution was reported by Goodwin et al [21].…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…A longer ureteral defect can be replaced using a segment of the intestines, usually the ileum (ileal interposition graft), in our department [7]. The first ileal ureter substitution was reported by Goodwin et al [21].…”
Section: Discussionmentioning
confidence: 88%
“…Open ileal ureteral substitution has some disadvantages, including greater trauma, longer recovery, and more complications. At present, minimally invasive techniques are often chosen, including laparoscopic surgery and robotic surgery [7,23], which have lower narcotic requirements, shorter hospital stays, and shorter times to convalescence. According to Table 1, mean operative time as shorter for MIS group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because we were trying to develop a convenient and efficient descriptive system of scoring and classification, and our previous statistical analysis showed that the patient's age, gender, and BMI have little effect on the complexity of the operation, we did not include these variables because we did not want a system that was cumbersome and difficult to calculate. Prior to the development of the scoring and classification system, we conducted an extensive review of studies to identify candidate variables that are clinically useful and have been shown to independently influence surgical decisions (6,(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%